Hydrological Analysis of TRMM (Tropical Rainfall Measuring Mission) Data in Lesti Sub Watershed - Suryaningtyas, Lufi Suryaningtyas; Ery, Suhartanto; Rispiningtati, Rispiningtati (Fakultas Teknik UB, 2020)
Alternative solution for availability of inadequate rain data as input to hydrological data is with the assist of TRMM (Tropical Rainfall Measurement Mission) satellite rainfall data which using remote sensing technology (satellite). The purpose of this study is to look for correlations and data corrections and validate TRMM satellite data with rainfall data at the rain station and discharge observation data. Lesti sub-watershed is used as a case study with consideration of the data availability that is considered sufficient. The validation results of corrected TRMM rain dataÂ produce Nash-Sutcliffe Efficiency (NSE), Root Mean Squared Error (RMSE), Correlation Coefficient (R), and Relative Error/Kesalahan Relatif (KR). Then, conducted an analysis of the flow discharge estimation using TRMM rainfall data and validated with Tawangrejeni AWLR (Automatic Water Level Record) data. The results of flow discharge validation using the FJ Mock Method produce an NSE value of 0,507, RMSE 19,383, Correlation Coefficient (R) 0,713, and Relative Error of 0,001. Overall analysis shows TRMM data can be used as an alternative of the rain data that is used to estimate flow discharge, but the result of flow discharge analysis is still better using rainfall data from the rain station post